2018
DOI: 10.1159/000491932
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Serum Thyroglobulin Level as a Useful Predictive Marker to Differentiate Thyroid Cancer

Abstract: Introduction: Thyroid cancer is the most common endocrine system cancer. Although fine-needle aspiration biopsy is the most commonly used method for diagnosis, it is not always sufficient. The aim of this study was to investigate the influence of preoperative serum thyroglobulin (Tg) concentration on differentiated thyroid cancer risk. Material and Methods: A total of 133 patients who underwent total thyroidectomy due to various indications at the Ear-Nose-Throat Department, Ataturk University Medical School, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Kim et al 24 retrospectively reviewed the clinical records of 4029 differentiated thyroid cancer cases and reported that preoperative Tg levels were significantly associated with tumor burden and tumor extent. In this study, we observed that serum Tg had very low sensitivity and high specificity, as reported previously 7 . This highlights the limitations of diagnosis based on a single parameter, highlighting the need for a combined diagnosis.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Kim et al 24 retrospectively reviewed the clinical records of 4029 differentiated thyroid cancer cases and reported that preoperative Tg levels were significantly associated with tumor burden and tumor extent. In this study, we observed that serum Tg had very low sensitivity and high specificity, as reported previously 7 . This highlights the limitations of diagnosis based on a single parameter, highlighting the need for a combined diagnosis.…”
Section: Discussionsupporting
confidence: 82%
“…In this study, we observed that serum Tg had very low sensitivity and high specificity, as reported previously. 7 This highlights the limitations of diagnosis based on a single parameter, highlighting the need for a combined diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kars et al. ( 18 ) found that the prevalence rate of thyroid cancer was higher with preoperative serum Tg >188.5 ng/ml. Wang et al.…”
Section: The Role Of Tg In Preoperative Patients With Dtcmentioning
confidence: 99%